Seismic safety assessment of existing masonry infill structures in Nepal - Hemchandra Chaulagain (2016)
Reinforced concrete (RC) buildings in Nepal are constructed with RC frames and masonry infi ll panels. Thesestructures exhibit a highly non-linear inelastic behavior resulting from the interaction between the panels and frames. Thispaper presents an extensive case study of existing RC buildings in Nepal. Non-linear analyses were performed on structuralmodels of the buildings considered as a bare frame and with masonry infi ll, in order to evaluate the infl uence of infi ll wallson the failure mechanisms. Five three-storey buildings with different structural confi gurations and detailing were selected.The effect of masonry infi ll panels on structural response was delineated by comparing the bare-framed response with theinfi ll response. Seismic performance is evaluated with regard to global strength, stiffness, energy dissipation, inter-storeydrift, and total defl ection of the structure. A parametric analysis of structures with masonry infi ll is also performed. Forthis, the infl uence of different material properties is studied, namely diagonal compressive stress, modulus of elasticity andtensile stress of masonry infi ll panels. Study results show that masonry infi ll increases the global strength and stiffness ofthe structures; it decreases the inter-storey drift and hence the total displacement of the structure. The results quantify theinfl uence of the infi ll panels on structural response and, in particular, the effect of the diagonal compressive strength of themasonry wall.